Temperature-controlled spectral tuning of full-color carbon dots and their strongly fluorescent solid-state polymer composites for light-emitting diodes. Issue 4 (28th January 2019) - Hu, Tantan; Wen, Zhuoqi; Wang, Chan; Thomas, Tiju; Wang, Chuanxi; Song, Qijun; Yang, Minghui
Abstract : Temperature-controlled, scalable synthesis of CA-based full-color CDs and subsequent fabrication of white-LEDs with CIE coordinates of (0.32, 0.33) and a CRI of 82.7. Abstract : The development of full-color/white carbon-dot-based light-emitting diodes (LEDs) has been achieved, which show promising applications in full-color and flexible displays, backlights, and novel lighting sources. The gram-level synthesis of these full-color carbon dots (CDs) from citric acid by controlling the temperature has been achieved. By increasing the temperature from 120 to 180 °C, two, four, and six light-emitting CDs can be obtained, for which the emission wavelength shifts from 440 to 585 nm. This result reveals that temperature has a huge impact on the evolution of surface states, that is, increasing the temperature brings about enhanced surface functionalization and passivation, resulting in a red shift of the emission wavelength and enhancement of quantum yield. Then, full-color CDs/polymer composite phosphors are fabricated for efficient phosphor-based LED devices with quench-resistant solid-state fluorescence. By regulating the proportion of various CDs/polymer phosphors, white LEDs are realized with Commission Internationale de L'Eclairage coordinates of (0.32, 0.33) and a color rendering index of 82.7. The as-prepared CD-based full/white color LEDs can prove to be promising candidates for alternative light sources.